2018
DOI: 10.4102/abc.v48i2.2324
|View full text |Cite
|
Sign up to set email alerts
|

Porcine zona pellucida vaccine immunocontraception of African elephant (Loxodonta africana) cows: A review of 22 years of research

Abstract: Background: The native porcine zona pellucida (pZP) vaccine has been successfully used for immunocontraception of wild horses, white-tailed deer and approximately 90 zoo species for more than 25 years.Objectives: To provide proof of concept and test contraceptive efficacy of pZP in African elephants. Once completed, test the population and behavioural effects on cows in the Greater Makalali Private Game Reserve (GMPGR). Following the GMPGR, test efficacy, population effects, safety and reversibility in 25 rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Elephant restorations may compromise biodiversity locally in some instances (Cook et al, 2017; Midgley et al, 2020), and active population control may be argued in these cases (Bertschinger et al, 2018), for example, when elephants completely prohibit tree recruitment throughout a conservation area (Cook et al, 2017). However, this is a limited overall challenge due to the widespread depression of elephant populations (Chase et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Elephant restorations may compromise biodiversity locally in some instances (Cook et al, 2017; Midgley et al, 2020), and active population control may be argued in these cases (Bertschinger et al, 2018), for example, when elephants completely prohibit tree recruitment throughout a conservation area (Cook et al, 2017). However, this is a limited overall challenge due to the widespread depression of elephant populations (Chase et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Shackleford mares treated with PZP change groups more often and join more groups than do untreated mares (Madosky et al, 2010; Nuñez et al, 2009); these behavioral effects can be long‐lasting, even after treatment has ended (Nuñez et al, 2017). PZP is used to control animal populations around the world, including white‐tailed deer ( Odocoileus virginianus ; McShea et al, 1997), elk ( Cervus canadensis ; Heilmann et al, 1998), the endangered African elephant ( Loxodonta africana ; Bertschinger et al, 2018), and Przewalski's horse ( Equus ferus przewalskii ; Kerekes et al, 2021). Our previous work on Shackleford has shown that fewer contraceptive treatments, over longer periods of time can help to maintain more natural behavior and reproductive physiology (Nuñez et al, 2017) and reduce stress (Nuñez et al, 2014); given the present data, such management practice could also potentially maintain important symbiotic relationships in treated mares.…”
Section: Discussionmentioning
confidence: 99%
“…Elephant bulls have been shown to cause greater impacts to vegetation compared with cows as they are larger bodied and have more destructive tendencies, especially when in musth (Greyling, 2004). The success of contraception as a management tool to control population numbers has been shown in several small reserves in South Africa, including the Greater Makalali Private Game Reserve and Tembe Elephant Park (Bertschinger et al, 2018). Contraceptives were also administered to bull elephants in 2016 in the reserve considered in this study.…”
Section: Discussionmentioning
confidence: 99%